Elevating STEM Learning: Unleashing the Power of AI in Open Distance eLearning - Shabalala, Nonkanyiso Pamella (Research in Social Sciences and Technology, 2024)
The integration of Artificial Intelligence (AI) into Open Distance eLearning (ODeL) represents a significant evolution in STEM education, offering transformative benefits in teaching, learning and administrative processes. This conceptual paper explores how AI-driven platforms are revolutionising ODeL by providing personalised learning experiences, real-time feedback, adaptive assessments and immersive simulations through technologies like Augmented Reality (AR) and Virtual Reality (VR). These advancements not only enhance student engagement and understanding but also support the development of critical thinking and problem-solving skills. The paper highlights successful case studies from institutions like Carnegie Mellon University and Stanford Online High School, showcasing practical implementations of AI in STEM education. However, the integration of AI also brings forth challenges, particularly concerning data privacy, security and the need for equitable access to technology. As AI continues to advance, it promises to play an important role in lifelong learning, offering modular and just-in-time educational opportunities. The paper concludes with a call for robust ethical frameworks to guide the responsible use of AI in education, ensuring that the benefits are maximized while potential risks are mitigated.